Air Pollution in India: Sources, Impacts and Policy Responses (Prakriti - The International Multidisciplinary Research Journal, 2026)
Air pollution is one of the most critical environmental and public health challenges confronting India in the 21st century. Rapid urbanization, industrialization, motorization, and unsustainable agricultural practices have resulted in dangerously high levels of air pollutants across much of the country. India today houses several of the world’s most polluted cities, with particulate matter (PM2.5 and PM10) levels routinely exceeding both national and international safety standards. The health, environmental, and economic consequences are profound, ranging from millions of premature deaths each year to crop yield losses, climate disturbances, and GDP reduction. This paper reviews the major causes of air pollution in India, outlines its wide-ranging impacts, and critically examines existing policy measures such as the National Clean Air Programme (NCAP). Using secondary data from government agencies, peer-reviewed journals, and global assessments, this research highlights both progress and persistent gaps. The paper concludes with policy recommendations that stress the importance of integrating technological solutions, governance reforms, and community engagement to address the air pollution crisis.
Keywords: Crises; Pollution; Climate; Resources; Reforms